Suprafoveal condylar arthroplasty in unilateral disc displacement without reduction – A retrospective study. Issue 2 (February 2023) - Shadamarshan R, Arunkumar; Sharma, Rohit; Agrawal, Nitesh; Patrikar, Seema
Abstract: The aim of this study was to evaluate the efficacy of suprafoveal condylar arthroplasty (SFCA) in the management of patients with unilateral temporomandibular joint (TMJ) disc displacement without reduction (DDWoR). A retrospective study comprising patients who underwent unilateral SFCA for clinically and radiologically confirmed unilateral DDWoR from 2008 to 2020 was conducted. Patients older than 18 years at the time of diagnosis with a minimum of 6 months of unsuccessful non-surgical and minimally invasive management (including diet and life style modification, physiotherapy, appliance therapy, pharmacotherapy, arthrocentesis and arthroscopic lysis and lavage) before undergoing surgery with a minimum of 1 year follow-up post-surgery were included in the study. Patients with other articular and extra-articular causes of restricted mouth opening, prior history of mandibular surgery and/or trauma, growth abnormalities, systemic, metabolic, infective, neoplastic conditions affecting TMJ, including gross occlusal disharmony, untreated existing para-functional habits and bilateral DDWoR, were excluded from the study. Patients were assessed in terms pain on a visual analog scale (VAS), interincisal mouth opening (MO) and subjective assessment of mandibular range of movements including deviation of mouth opening, protrusion and ability for contralateral laterotrusion. 23 patients (10 males and 13 female) were included in the study, with a mean age of 35.09 years and mean follow up period of 37.7 months (range = 12–58; SD = 15.3). The mean pain scores on the VAS reduced from 6.35 preoperatively to 1.13 postoperatively and were found to be statistically significant (p < 0.0001). The improvement of the mean pre-operative mouth opening of 21.83 mm to a mean post-operative mouth opening of 42.09 mm was also found to be statistically significant (p < 0.0001). The subjective improvement in protrusive (p = 0.0003), laterotrusive (p = 0.0005) and opening movements (p = 0.0001) after 1 year were also found to be statistically significant. No patient developed any significant changes in occlusion post-operatively. Four of 23 (17.3%) patients developed transient neuromotor deficit of the temporal branch of the facial nerve. Within the limitations of the study, it seems that SFCA (without addressing the disc) might be an alternative to less invasive treatment approaches, if the latter turned out not to be successful.